A strategy for the implementation of water-quality-based discharge limits for the regulation of hazardous substances - GÜRSOY HAKSEVENLER, BETÜL HANDE (SPRINGER HEIDELBERG, 2021)
Many developing countries apply technology-based discharge standards that set quantitative limits on pollutant discharges. These standards do not inherently consider ambient constraints and, therefore, cannot guarantee to protect aquatic life from hazardous pollutants. It is a challenge for developing countries to enforce water-quality-based limits for wastewater discharges and guarantee the intended use of water. This study aims to develop a strategy that suits the needs of developing countries for a transition from technology-based discharge standards to water-quality-based discharge limits. To this end, a pilot monitoring program was carried in the Gediz River Basin in Turkey. Surface water, industrial, and urban wastewater samples were collected and analyzed for 45 priority pollutants identified by the European Union and 250 national river basin specific pollutants. The monitoring results revealed that the environmental quality standards (EQSs) were exceeded for 8 priority, and 28 specific pollutants. This finding indicated that the existing technology-based discharge standards are not satisfactory to guarantee the intended water quality, and there is a need for adopting a new strategy for the implementation of water-quality-based discharge limits in Turkey. As a widely applied approach for determining water-quality-based discharge limits, firstly, conservative mass balance with and without consideration of mixing zone was evaluated. The results indicated that this approach was not applicable due to the receiving environment concentrations being higher than the EQSs. As an alternative approach, the dilution methodology, which considers the level of dilution occurring at the immediate discharge point, was tested. The results proved that the dilution methodology is the most appropriate strategy for developing countries with relatively poor surface water quality to improve the water quality to the level where the conservative mass balance approach can be applicable.
Keywords: Dilution factor; Discharge Test Software; Hazardous substances; Environmental monitoring; Environmental quality standards; Water Framework Directive; Water-quality-based discharge limits; DEVELOPING-COUNTRIES; GEDIZ RIVER; STANDARDS; EFFLUENTS; POLLUTION